The path to market success for dynamic spectrum access technology. - Chapin, John M. (IEEE Communications magazine)
Rapid progress is being made in the technology for dynamic spectrum access (DSA) radio systems. However, the structure and dynamics of the wireless services market must also evolve for DSA to succeed. This article examines the interlinked technical and economic issues associated with markets for DSA-based wireless services. We use this analysis to make technical and policy recommendations supporting the commercial success of DSA technology.